A review of pharmacotherapy for chronic low back pain with considerations for sports medicine - Peniston, J. H. (The Physician and Sportsmedicine, 2012)
Up to 30% of athletes experience low back pain (LBP) depending on sport type, sex, training intensity and frequency, and technique. United States clinical guidelines define back pain as chronic if it persists for = 12 weeks, and subacute if it persists 4 to < 12 weeks. Certain sports injuries are likely to lead to chronic pain. Persistent or chronic symptoms are frequently associated with degenerative lumbar disc disease or spondylolytic stress lesions. Exercise therapy is widely used and is the most conservative form of treatment for chronic LBP (cLBP). Pharmacotherapies for cLBP include acetaminophen, nonsteroidal anti-inflammatory drugs, and opioids. Acetaminophen is a well-tolerated first-line pharmacotherapy, but high-dose, long-term use is associated with hepatic toxicity. Nonsteroidal anti-inflammatory drugs can be an effective second-line option if acetaminophen proves inadequate but they have well-known risks of gastrointestinal, cardiovascular, and other systemic adverse effects that increase with patient age, dose amount, and duration of use. The serotonin-norepinephrine reuptake inhibitor, duloxetine, has demonstrated modest efficacy and is associated with systematic adverse events, including serotonin syndrome, which can be dose related or result from interaction with other analgesics. Opioids may be an effective choice for moderate to severe pain but also have significant risks of adverse events and carry a substantial risk of addiction and abuse. Because the course of cLBP may be protracted, patients may require treatment over years or decades, and it is critical that the risk/benefit profiles of pharmacotherapies are closely evaluated to ensure that short- and long-term treatments are optimized for each patient. This article reviews the clinical evidence and the guideline recommendations for pharmacotherapy of cLBP.